Rekonstruksi Pengaturan Perkawinan Anak Dibawah Umur Berbasis Nilai Keadilan - Kasmudin Kasmudin (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2019)
The aim of this study is to describe how the marriage arrangements of minors in the perspective of Law No. I of 1974 concerning marriage, how the weaknesses in the arrangement of the marriage of minorstoday, and how the reconstruction of the marriage arrangements of minors are based on justice values. The approach of this study is sociological juridical method   by applying justice as a grand theory, legal protection as a middle range theory, and legal system   as applied theory. The result research showed, the marriage arrangements of underage children is through Law No. 1 of 1974no longer relevant in regulating and resolving the complexity of the legal problems of modern life today and it needs a construction. The construction based on existing needs, situations and conditions. Efforts to reconstruct the age limit of marriage by changing the age limit (clause) in marriage regulations from a minimum age of 16 years for women and 19 years for men is reduced to 15 years for women and 17 years for men (by revising article 7 paragraph 1 which mentions 19 years for men and 16 years for women and there is no need for dispensation as mentioned in article 7 paragraph 2). The need to reduce the age limit of marriage is based on assumptions, (1) the existence of promiscuity that has been difficult to avoid, (2) the development of maturity (psychic) children are increasingly rapid with the massive development of information technology, (3) consideration of parents' economic factors, and (4)  religious and cultural of society. Keywords: reconstruction, underage marriage, justice value